PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK IPA BERBASIS PENDEKATAN SAINTIFIK UNTUK SISWA KELAS V SD NEGERI PONCOWARNO KABUPATEN KEBUMEN - Rifqiyatun Nihayah; Yuli Prihatni (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study aims to develop LKPD products with a scientific approach to the subject of ecosystems for fifth-grade students of SD Negeri Poncowarno. In addition, this study also aims to determine the feasibility of the LKPD, as well as knowing the responses of students to LKPD products. This research was conducted in Poncowarno State Elementary School with a sample of class V which was 23 students. The research method used in this study is the method Research and Development (R & D). The results showed that the developed LKPD received a very good rating from expert lecturers. The percentage of media expert validation was 92%, material experts 92%, linguists 89% and class teachers 89%. Limited field trials show that student responses are very good at 88%. LKPD based on a scientific approach that has been developed can help students learn ecosystem material in science subjects.